Does Partisanship Shape Attitudes toward Science and Public Policy? The Case for Ideology and Religion. Issue 1 (March 2015) - Blank, Joshua M.; Shaw, Daron
Despite the apparent partisan divide over issues such as global warming and hydraulic fracturing, little is known about what shapes citizens' willingness to accept scientific recommendations on political issues. We examine the extent to which Democrats, Republicans, and independents are likely to defer to scientific expertise in matters of policy. Our study draws on an October 2013 U.S. national survey of 2, 000 respondents. We find that partisan differences exist: our data show that most Americans see science as relevant to policy, but that their willingness to defer to science in policy matters varies considerably across issues. While party, ideology, and religious beliefs clearly influence attitudes toward science, Republicans are not notably skeptical about accepting scientific recommendations. Rather, it seems that Democrats are particularly receptive to the advice and counsel of scientists, when compared to both independents and Republicans.